Hypoglycemic properties of ethanolic extracts of Gongronema latifolium, Aloe perryi, Viscum album and Allium sativum administered to alloxan-induced diabetic albino rats (Rattus norvegicus) - CO, Ibegbulem; PC, Chikezie (Pharmacognosy Communications)
Background: Plants offer a wide range of natural compounds of medicinal values to humans and domestic animals. Objective: The ethanolic extracts of Gongronema latifolium, Aloe perryi, Viscum album (leaves) and Allium sativum (bulb) were investigated for their phytochemical/biochemical constituents and hypoglycemic properties. Materials and Methods: Hypoglycemia was induced in rats by a single dose (140 mg/kg) of intra-peritoneal injection of alloxan monohydrate in citrate buffer (pH 4.5). Suspensions of the ethanolic extracts were administered by intraperitoneal injection at doses of 2 mg/kg every 16 h for 54 h. Collection of blood samples for estimation of fasting blood glucose (FBG) was carried out at regular time intervals of 0, 16, 32, 48 and 54 h, using the glucose oxidase method. Results: Phytochemical and biochemical screening showed the presence of saponins, tannins, flavonoids, proteins and carbohydrates in the four plant tissues under investigation. A. sativum and G. latifolium also tested positive for the presence of alkaloids. The capacities of the four ethanolic extracts to reduce FBG concentrations in treated rats at the 54 h were in the order: A. perryi > G. latifolium > A. sativum > V. album. Comparatively, at t = 16 h, FBG concentration of V. album treated rats was not significantly different (p > 0.05) from those of G. latifolium treated group. Likewise, FBG concentration of rats treated with V. album extract did not show a significant difference (p > 0.05) compared to the group administered with extract of A. sativum. Conclusion: The four plant extracts used in the present study exhibited approximately the same capacity to act as hypoglycemic agents in the treated rats and correlate with the therapeutic capacity of the standard drug, glimepiride.
Keywords: Hypoglycemia; phytochemical; A. perryi; G. latifolium; A. sativum; V. album; glimepiride